Reputasi KAP & Komite Audit pada Integritas Laporan Keuangan Dimoderasi Komisaris Independen & Kepemilikan Institusional - Ardian Christiana; Widaryanti Widaryanti; Luhgiatno Luhgiatno (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2021)
This study aims to analyze the effect of the reputation of KAP and the audit committee to integrity of financial statements with independent commissioners and institutional ownership as moderating variables. This study uses secondary data from the annual reports. The population in this study were real estate and property companies listed on the Indonesia Stock Exchange for the period 2016-2018. The sampling technique used was purposive sampling and the number of samples was 32 companies. Methods of data analysis using the SPSS 26 program. The results of this study indicate that the reputation of KAP has a positive effect to integrity of financial statements. The audit committee has no effect to integrity of the financial statements. Independent commissioners do not moderate the influence of KAP reputation and audit committee to integrity of financial statements. Institutional ownership moderates the effect of KAP reputation to integrity of financial statements. Institutional ownership moderates the effect of audit committee to integrity of financial statements. The reputation of KAP and the audit committee has a simultaneous effect to integrity of financial statements.